(untitled) (Stamford Journal of Microbiology, 2013)
Vibrio cholerae serotype O1 causes diarrhea in many developing countries around the world. In most cases, cholera patients pose some sorts of immunity against the naturally occurring infection. In the present study, the bactericidal activity of the sera of rabbit immunized with whole cell extract of Vibrio cholerae O1 was investigated. The protein profile of the serotype exhibited 20 types of proteins of distinguished molecular weights. The western blot analysis revealed at least 10 proteins to be immunogenic. Interestingly, decomplementation of the sera was found to abolish the bactericidal activity. The bactericidal activity of non immunized rabbit sera was also investigated and the results revealed that the immunized sera were more effective than that of non immunized one. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15209 Stamford Journal of Microbiology, Vol.2(1) 2012: 24-27